Arabinogalactan Proteins From Baobab and Acacia Seeds Influence Innate Immunity of Human Keratinocytes In Vitro. Issue 9 (10th April 2017) - Zahid, Abderrakib; Despres, Julie; Benard, Magalie; Nguema‐Ona, Eric; Leprince, Jerome; Vaudry, David; Rihouey, Christophe; Vicré‐Gibouin, Maité; Driouich, Azeddine; Follet‐Gueye, Marie‐Laure
Abstract : Plant derived arabinogalactan proteins (AGP) were repeatedly confirmed as immunologically as well as dermatologically active compounds. However, little is currently known regarding their potential activity toward skin innate immunity. Here, we extracted and purified AGP from acacia ( Acacia senegal ) and baobab ( Adansonia digitata ) seeds to investigate their biological effects on the HaCaT keratinocyte cell line in an in vitro system. While AGP from both sources did not exhibit any cytotoxic effect, AGP from acacia seeds enhanced cell viability. Moreover, real‐time quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) analysis showed that AGP extracted from both species induced a substantial overexpression of hBD‐2, TLR‐5, and IL1‐α genes. These data suggest that plant AGP, already known to control plant defensive processes, could also modulate skin innate immune responses. J. Cell. Physiol. 232: 2558–2568, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Real‐time quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) analysis showed that AGP extracted from acacia or baobab seeds induced a substantial overexpression of hBD‐2, TLR‐5, and IL1‐α genes. These data suggest that plant AGP, already known to control plant defensive processes, could also modulate skin innate immune responses.